The commitment of a academic management with the public university: affective, instrumental and regulatory relations (Research, Society and Development, 2021)
The present work has the objective of investigating the commitment of academic managers in the public university. The research population was composed by 80 managers, with 46 respondents as the sample. The questionnaire applied is composed of the sociodemographic profile and the scale of organizational commitment developed by Meyer, Allen and Smith (1993). The data analysis is done through descriptive statistics and the content analysis technique, useful in interpreting the results, since it better clarifies the quantitative data.  The results demonstrate high affective commitment, while normative and instrumental are equivalent in statistical terms, which is the key point of the research, object of deeper analysis. Managers demonstrate a willingness to remain and identify with the university, which is the main characteristic of the affective base of commitment. There is a bond between the server and the institution that is not exclusively the professional. The normative basis is basically expressed by loyalty. Gratitude is built over time at work, as the bond between the worker and the organization is consolidated. The instrumental base demonstrates that managers are at the university more by will than by necessity. The professor got where he wanted in terms of career, and assumed a public role as coordinator of the undergraduate course, inferring from this that he has no interest in working at another public university, since the legal guarantees are the same. These resulting data lead to reflection on the complex connections between professors and universities, giving rise to further research in the future to continue the theme.